2012
DOI: 10.1523/jneurosci.4137-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Default State-Associated Inhibition during Repetition Priming Improves Response Articulation

Abstract: Behavior is a product of both the stimuli encountered and the current internal state. At the level of the nervous system, the internal state alters the biophysical properties of, and connections between, neurons establishing a “network state”. To establish a network state, the nervous system must be altered from an initial default/resting state, but what remains unclear is the extent to which this process represents induction from a passive default state or the removal of suppression by an active default state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…3 B ; t =1.716; df=5; p =0.1468; n =6). However, as reported previously (Dacks et al, 2012), CBI-2 stimulation in HiDi did increase B8 excitability ( t = 12.31; df = 5; p < 0.001; n =6), indicating that in these preparations CBI-2 was capable of modulating neuronal excitability. The decrease in B4/5 excitability was likely due to their activity during motor programs as we found that B4/5 excitability decreased after repeated EN programs (Fig.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…3 B ; t =1.716; df=5; p =0.1468; n =6). However, as reported previously (Dacks et al, 2012), CBI-2 stimulation in HiDi did increase B8 excitability ( t = 12.31; df = 5; p < 0.001; n =6), indicating that in these preparations CBI-2 was capable of modulating neuronal excitability. The decrease in B4/5 excitability was likely due to their activity during motor programs as we found that B4/5 excitability decreased after repeated EN programs (Fig.…”
Section: Resultssupporting
confidence: 84%
“…CBI-2 priming increases B8 excitability (Dacks et al, 2012) which could serve as an additional contributing factor to the increased B8 protraction firing rate in EN programs. Consistent with this, the number of spikes elicited from B8 during 10 s of 5 Hz B65 spiking increased post-CBI-2 priming (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An assumption is that a response is not initiated until facilitatory inputs to the alpha motoneuron pool exceed inhibitory levels. In the lead up to a response, impulse control mechanisms [2022] keep the motoneurons below threshold until a movement is appropriate. This framework is consistent with models of saccades whereby the growth of activity in neurons predicts saccade initiation time [23].…”
Section: Methodsmentioning
confidence: 99%
“…For egestion they are closed during protraction and open during retraction. However, when a single cycle of a motor program is triggered in a rested preparation neither ingestion, nor egestion is observed [4246]. Instead motor programs are not well articulated, and are referred to as having ‘intermediate’ characteristics.…”
Section: Network Degeneracy and Experience Dependent Plasticitymentioning
confidence: 99%